PENGARUH PELAYANAN MUDLARABAH TERHADAP TINGKAT KEPUASAN ANGGOTA KOPERASI DAN MASYARAKAT KOPERASI BHAKTI PERTIWI ABADI JAKARTA TIMUR - Abdullah Fathoni (Jurnal Ekonomi dan Industri, 2021)
Syaria economy is part of global industry. Every country in the world has a different background in establishing the country, for instances different values, differences in natural resources, and others. For this reason, the approach used to elaborate each of the problems will be different because different country has different methods to face the economic globalization. Compromising the rationality of the cooperative economic thoughts and the sharia economics is a method to find a new balance point between local wisdom, national ideals, and the values of the Indonesian nation in responding to economic globalization. There are two approaches used in this paper. Firstly, "field study" or direct observation on the object of research which are the cooperatives. Secondly, approaching to the sharia economic agents and the academics, termed as "librarian study", in which to conduct a literature review with several book references in the author's personal library. The systematics used in this study are as follows; first, to formulate an academic study of the problems surrounding Indonesia's economic development and to formulate the contemporary economic challenges. Second, bring the formulation result to be a point for discussion in campus at undergraduate and postgraduate level. Third, bring the discussions result as a point for discussion and study among experts in cooperative economics and sharia economics. Fourth, find the references against the results of the study's third phase according to the literature study. Fifth, writing scripts or papers with various academic empirical studies. From the results of the study above, it can be concluded that Indonesian must formulate their own future steps to face economic globalization, based on their own national identity as formulated in the values contained in Pancasila and Article 33 of the 1945 Constitution.